Socio-Cultural Dimension of EFL Writing Feedback in Indonesian - Danafi Danafi (Language-Edu, 2021)
In the writing feedback process, pupils are more passive role to participating in the writing process. Furthermore, there is a dearth of debate on how social-cultural attitudes impact teacher feedback. Moreover, in Indonesia closes to the dimension of socio-cultural.The purpose of this research is to know the socio-cultural dimensions which were reflected on EFL learners that mediated by MLE and AT theory. The data are collected by interviewing two lecturers, students, and analyze writing draft of students in University level, exactly in English Department of University Islam of Malang. The data found that, by MLE and AT theory, teacher or lecturer should involve the role of students to be more active in the process of writing feedback in order to the mission in the writing task can be reached between students and lecturer. Additionally, the intervention to the school administration also made lecturer do that as the responsibility to give the scores as development ability of students to the next semester or in the future and play an active role in providing purposive, valuable, effective, and flexible feedback in writing process orientation classes, and also importance role of students in teacher-student dialogue mediation.